Dynamic Transmission Policy for Multi-Pair Cooperative Device-to-Device Communication With Block-Diagonalization Precoding - Wang, Yung-Shun; Hong, Y.-W. Peter; Chen, Wen-Tsuen (IEEE transactions on wireless communications, 2019)
This paper proposes a dynamic precoding and power allocation policy for mutually cooperative device-to-device (D2D) transmitter-receiver pairs that underlay a cellular system in the uplink. The cooperative transmission consists of two phases: a data-sharing phase (i.e., phase 1) and a joint transmission phase (i.e., phase 2). Multicast precoders are used in phase 1 and coordinated block-diagonalization precoders are considered in phase 2. The precoders are jointly designed to maximize the long-term utility of the D2D users subject to long-term individual power and rate-gain constraints and an instantaneous interference constraint at the base-station. The long-term objective and constraints allow cooperating users to adapt their resources more flexibly over time, but increase the complexity of the design. By adopting the Lyapunov optimization framework and by constructing virtual queues to record the temporal evolution of the system states, the long-term utility maximization problem can be decoupled into a series of short-term weighted-rate-minus-energy-penalty (WRMEP) optimization problems that can be solved efficiently. A low-complexity algorithm is further proposed for solving the WRMEP problem when multicasting in the data-sharing phase is performed by a spatially white input. Theoretical performance guarantees and a bound on the virtual queue backlogs are also derived.